High-throughput sequencing and analysis of chromosome one of Eimeria tenella (Houghton strain) - Ling, King Hwa; Rosli, Rozita; Shamsudin, Mariana Nor; Mohamed, Rahmah; Wan, Kiew Lian (Penerbit Universiti Sains Malaysia, 2004)
Eimeria tenella is one of the most common Eimeria species that causes coccidiosis. This species is also highly pathogenic and it is the most common species occurring in the field. Eimeria tenella is also related to other protozoan parasites placed under the same phylum such as Plasmodium falciparum, Toxoplasma gondii and ryptosporidium